2013
DOI: 10.1002/2327-6924.12052
|View full text |Cite
|
Sign up to set email alerts
|

Managing asthma during pregnancy

Abstract: Purpose Pregnant women with asthma have many concerns about their respiratory health, as well as the health of their baby. A woman's respiratory system experiences many physiological changes during pregnancy and when a diagnosis of asthma is present, the clinical effect of pregnancy on asthma is variable. Regardless of disease years, when asthma patients become pregnant, both patients and healthcare providers want to know how pregnancy affects asthma and how asthma may affect pregnancy outcomes. This article w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…29 Given this, guidelines recommend that women requiring pharmacological management continue their asthma medication during pregnancy. 30,31 It is therefore concerning that a number of asthma medications (ATC R03) were identified as being used relatively less among pregnant women. This includes a number of inhaled corticosteroids (ATC R03BA, R03AK), which are the most effective preventive asthma medications, 32 and are likely to have low teratogenic potential because they are inhaled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Given this, guidelines recommend that women requiring pharmacological management continue their asthma medication during pregnancy. 30,31 It is therefore concerning that a number of asthma medications (ATC R03) were identified as being used relatively less among pregnant women. This includes a number of inhaled corticosteroids (ATC R03BA, R03AK), which are the most effective preventive asthma medications, 32 and are likely to have low teratogenic potential because they are inhaled.…”
Section: Discussionmentioning
confidence: 99%
“…Those with the largest associations were insulin (isophane human; RR = 10.4, 95% CI = 9.6-11.3), methyldopa (RR = 9.2, 95% CI = 8.4-10.2), ordinary salt combinations, an antacid, (RR = 7.6, 95% CI = 7.0-8.3) and folic acid (RR = 7.0, 95% CI = 6.7-7.4). The majority of medications which were significantly more commonly dispensed to pregnant women compared to matched control women had a risk categorisation of A or were T A B L E 1 Characteristics for the pregnancy cohort (concessional beneficiaries) and the whole population of pregnancies (concessional and general beneficiaries) conceived from 1 January 2006 and resulting in birth in NSW on or before 31 Stratification by age identified no additional category B, C or D medications that were more likely to be dispensed to pregnant women than women of childbearing age. Stratification by trimester, however, revealed significantly higher risk of a prochlorperazine (category C) dispensing during trimester 1 (RR = 1.4, 95% CI = 1.4-1.5) compared to the matched period among the control women (see Table S3).…”
Section: Medications During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic poorly controlled asthma during pregnancy leads to maternal hypoxemia, which directly or indirectly reduces the supply of the fetus with oxygen (5,6). Therefore, untreated asthma increases the risk of congenital malformations, low birth weight, preterm birth and perinatal mortality (1,(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Asthma medication mainly includes inhaled corticosteroids and bronchodilators (3,6,(12)(13)(14)(15)(16). The administration of corticosteroids during pregnancy has been associated with congenital malformations in children in some epidemiological studies (1,(17)(18)(19), while no association has been reported by others (9,10,(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%